Peningkatan Mutu Pesantren Melalui Penerapan Manajemen Sumber Daya Manusia - Mashuri Toha; Parisi Parisi (Universitas Al-Amien Prenduan, 2020)
The existence of pesantren in Indonesia is very important. This is because pesantren have made an important contribution in educating the Indonesian people. However, pesantren need to communicate with the times so that they can become educational institutions that can produce graduates who can compete in the midst of society. This needs to be done even though pesantren has its own uniqueness, both from the way and view of life adopted, the values that are followed, and the internal hierarchy of power that is adhered to by its inhabitants, making pesantren a sub-culture in Indonesia. This qualitative research seeks to reveal how the efforts of the Kembang Kuning Islamic Boarding School in Pamekasan, East Java, in improving the quality and quality of education and its management by maximizing human resource management. This pesantren has made efforts to plan, organize, direct and control its teachers and education personnel properly to improve the quality and quality of education and its management.